2021
DOI: 10.31851/hon.v4i1.5106
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Model Passing Bawah Bola Voli Pada Atlet Pemula Mahasiswa Universitas Islam Kalimantan MAB Kalimantan Selatan

Abstract: Penelitian ini bertujuan untuk : (1) bentuk model passing bawah bolavoli pada atlet pemula mahasiswa Uniska MAB Banjarmasin. (2) Hasil pelaksanaan tahap uji coba pada kelompok kecil dan kelompok besar model passing bawah bolavoli pada atlet pemula mahasiswa uniska MAB Banjarmasin. Metode penelitian yang digunakan yaitu penelitian pengembangan atau R&D. Hasil penelitian yang diperoleh yaitu (1) Tersusunnya 10 bentuk model passing bawah bolavoli dalam pembelajaran passing bawah bolavoli dengan unsur meliputi: Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…(2) by implementing the models that had been developed by the researcher, the students are actively motivated in participating the learning process. Pratiwi and Anggara (2021) carried out the study on underhand pass in volley ball novice athlete. From the study, they gathered not only the positive response and the models that are applicable to the novice athlete, but also found that this revealed that it impacts positively to the students.…”
Section: Evaluate Stagementioning
confidence: 99%
See 1 more Smart Citation
“…(2) by implementing the models that had been developed by the researcher, the students are actively motivated in participating the learning process. Pratiwi and Anggara (2021) carried out the study on underhand pass in volley ball novice athlete. From the study, they gathered not only the positive response and the models that are applicable to the novice athlete, but also found that this revealed that it impacts positively to the students.…”
Section: Evaluate Stagementioning
confidence: 99%
“…It focused on the technique and direct teaching. Furthermore, Pratiwi and Anggara (2021)a did the study on volleyball underhand pass model of novice athlete in Universitas Islam Kalimantan, Banjarmasin. This study created at least ten exercise models of volley ball underhand pass, including passing attitude, strategy, exercise model, and exercise variations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the development of the upper pass model, namely (Rohendi, 2020) where the development of a learning model for playing volleyball based on the results of his research on the game of volleyball increased using this model, then research from it can be improved through double-control upper pairing exercises in pairs, then other research on volleyball, namely (Marsiyem, Destriana, & Pratama, 2018) (Pratiwi & Anggara, 2021) in the underpass model of volleyball for beginner athletes, students of UNISKA MAB Banjarmasin, has received a positive response and can be applied to beginner athletes of UNISKA MAB Banjarmasin students, next research (Daryono & Almy, 2021) on self-check style affects the results of volleyball skills, based on the results of research that has been done there is an increase in volleyball playing skills through shelf check style training, an increase in volleyball service skills, an increase in passing skills and an increase in volleyball smash skills. Previous research on upper passing has not seen any research on the development of overhead pass learning for junior high school students, so this study will develop a overhead passing learning model of volleyball in Class VIII students at Junior High School No 1 Palembang.…”
Section: Introductionmentioning
confidence: 99%
“…High achievement is achieved not only because of the athlete's talent, but also because of external factors, namely training. Exercise is a very important factor in the effort to hone these talents to the maximum, therefore training must be done intensively and programmed (Pratiwi & Anggara, 2021) In the world of education, tennis learning has been carried out for a long time, various types of techniques are studied in sports colleges, these techniques require good basic movement skills, in tennis there are aspects of basic motion Gusril (2017), basic motion includes the following 1. Locomotor motion, which is motion that moves from one place to another, in tennis, for example, such as stepping, shifting, running and jumping.…”
Section: Introductionmentioning
confidence: 99%